ANTECEDENT AND CONSEQUENCES OF CAAT ON AUDIT QUALITY - Nahdho Ibnu Daham; Marita Kusuma Wardani (Jurnal Akuntansi Kontemporer, 2026)
Research Purposes. This study examine how perceived usefulness and perceived ease of use, as the core dimensions of the Technology Acceptance Model (TAM), influence auditors’ actual use of Computer-Assisted Audit Techniques (CAAT) and how such usage affects audit quality. Research Methods. This study employs a quantitative approach using Partial Least Squares Structural Equation Modeling (PLS-SEM) based on data collected through a questionnaire survey of 72 external auditors from Non-Big Four public accounting firms in Indonesia. Research Results and Findings. The results indicate that perceived usefulness and perceived ease of use have a positive effect on the actual use of CAAT, perceived ease of use positively influences perceived usefulness, and the actual use of CAAT positively affects audit quality. These findings imply that increasing auditors’ acceptance of CAAT through improving usability and perceived benefits can enhance audit quality, contributing to the development of auditing practices and literature, particularly in the context of Non-Big Four firms.